Characterization of LDPE-film by Experiments and Simulations - Kvarnmyr,Daniel; Pettersson,Simon (ISRN LUTFD2/TFHF-16/5210-SE(1-88), 2016)
In this thesis, the mechanical properties of thin films of low density polyethylene were investigated. There were three main objectives: to perform experiments, to simulate the experiments in Abaqus and to identify material parameters for some constitutive models by optimization. The experimental part consisted of conventional uniaxial tensile tests. Another objective was to investigate whether the thin films could be used with a biaxial tensile machine in conjunction with Digital Image Correlation (DIC). Digital image correlation provides the entire strain field, rather than a single stress-strain curve and thus provides a lot more information than a simple tensile test. The biaxial tensile machine was used successfully in combination with DIC for the thin films. It was found that polyethylene has a rate dependent stress-strain relationship and initially isotropic in-plane properties. At larger strains, however, there was a clear difference in properties in the two in-plane directions. Moreover, there was substantial plastic straining. The models available in Abaqus proved insufficient to model these phenomena. It seems that a customized user defined material must be developed to mimic the experimental results. Finally, a script was written to minimize the discrepancy between the experimental and simulated strain field, as well as the reaction forces. This script was used to calibrate one of the material models with respect to experimental results.
Keywords: LDPE; DIC; biaxial tension